DESIGN AND CONSTRUCTION OF ORBITA PROTECTION EQUIPMENT FOR PANORAMIC EXAMINATION - Indah Puspita, Mega; S.Si, M.Pd, Bagus Abimanyu; Handoko, Bagus Dwi; Wibowo, Ardi Soesilo; Darmawan, Erwin; isnoviasih, Susi tri; Fitriana, Ella (Journal of Applied Health Management and Technology, 2024)
Panoramic dental radiography uses X-rays to produce radiographs of the jaw and facial structures, from the teeth to the TMJ and the entire dental arch. Exposure to X-rays during an examination can be problematic because sensitive areas such as the thyroid gland and eyes adjacent to tooth structure also receive radiation exposure. Patients in panoramic examinations do not use eye radiation protection equipment for the orbit, namely Pb glasses, while the eyes are close to the dental arch which can receive radiation exposure, so eye radiation protection equipment is needed in panoramic examinations for patient safety. The aim of the research is to determine the function test and performance test of the Eye Radiation Protection Device.This type of research is quantitative research with an experimental approach. The research sample was 3 patients with variations of 3 kV: 70, 76, and 86 kV with a setting of 10 mA. The radiation dose to the eye was measured using a phantom and pocket dosimeter before and after using the radiation protection design tool, then looking for the average, difference and percentage and carrying out the Kruskal-Wallis spss test.The results of the three radiographs showed no artifacts, the exposure factor before using the device was 70 kV = 0.08 mSv, 76 kV = 0.17, 86 kV = 0.27 mSv while the radiation dose received after using the device with an exposure factor of 70 kV = 0 mSv, 76 kV = 0.86 kV = 0.003 mSv, while from the Kruskall-walls statistical test pre-test and post test kV 70 shows a significant value of 0.034 <0.05, kV 76 does not show a significant value of 0.121 > 0.05, kV 86 shows a significant value of 0.043 <0.05. The design of this eye radiation protection device has succeeded in reducing or reducing the radiation dose around the eyes by up to 100%. Meanwhile, the level of feasibility of the tool has a respondent score of 80%. Suggestions for using a thermoluminescence radiation measuring instrument (TLD) with smaller units, namely ÂµSv.